Christianity and Empire Revisited - Stanley, Brian (Religious Studies, Theology and Philosophy E-Books Online, Collection 2026., 2025)
The provision of balanced diets accounts for the major cost in intensive livestock production and to maximise profits requires continuous improvement in all aspects of dietary formulation. Consequently, throughout the world, considerable scientific effort is devoted to bringing about a better description of the nutrient content of diverse feedstuffs, to understanding the mode of action of anti-nutritional factors, to improving the description of nutrient requirements and to developing refined technologies for feed formulation, processing and provision. Feed evaluation science is a rapidly developing high technology field, with feed compounders, nutritionists, advisors and producers needing to keep abreast of rapid innovation. This text, written by a team of international authorities, covers basic principles and new developments in feed evaluation for simple-stomached animals with an emphasis on pigs and poultry. The topics of nutrient analysis and characterisation, nutrient bioavailablility, post-absorptive nutrient utilisation, modern approaches to the estimation of nutrient requirements (including growth modelling) are all covered in depth. Recent advances in feed evaluation for pigs, poultry and companion animals are highlighted. The work is essential reading for anyone needing to remain at the forefront of technological developments in feed evaluation.